Between autonomy and representation: toward a post-foundational discourse analytic framework for the study of horizontality and verticality - Seongcheol Kim (Critical Discourse Studies, 2022)
This paper sets out to think the relationship between horizontality and verticality from the perspective of post-foundational discourse theory, taking as a starting point the diachronic development from Laclau's and Mouffe's joint work on radical democracy to Laclau's theory of populism. The argument here is that the shift in conceptual terrain from the autonomy of `democratic struggles' to the representative function of `empty' popular signifiers points to deeper shifts and slippages – especially around the category of antagonism – as well as a more general tension between a horizontal politics of autonomy and a vertical politics of representation, for which radical democracy and populism respectively take on a paradigmatic character. While horizontality is predicated on the autonomous multiplicity and `multiplication of antagonisms', verticality entails the simplification and concentration of antagonism around central representative signifiers. The question thus becomes how antagonism is organized, or – drawing on Nonhoff's concept of contrariety – to what extent the contrarieties defining the constituent parts of an equivalential chain are more multiple or more concentrated. This is followed by empirical considerations on how horizontality and verticality are organizationally mediated within current political projects, including a distinction between movement parties and 'Volksparteien neuen Typs' (`people's parties of a new type').
Keywords: 320; horizontality; movement parties; populism; radical democracy; verticality